2009
DOI: 10.1104/pp.108.135129
|View full text |Cite
|
Sign up to set email alerts
|

VTC4 Is a Bifunctional Enzyme That Affects Myoinositol and Ascorbate Biosynthesis in Plants      

Abstract: Myoinositol synthesis and catabolism are crucial in many multiceullar eukaryotes for the production of phosphatidylinositol signaling molecules, glycerophosphoinositide membrane anchors, cell wall pectic noncellulosic polysaccharides, and several other molecules including ascorbate. Myoinositol monophosphatase (IMP) is a major enzyme required for the synthesis of myoinositol and the breakdown of myoinositol (1,4,5)trisphosphate, a potent second messenger involved in many biological activities. It has been show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
141
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 137 publications
(149 citation statements)
references
References 54 publications
(72 reference statements)
7
141
1
Order By: Relevance
“…Evidence exists that a minor pathway to ascorbic acid synthesis could proceed via myo-inositol synthesis (Baig et al, 1970;Radzio et al, 2003;Lorence et al, 2004;Torabinejad et al, 2009). We have previously shown that the vtc4 mutant (Conklin et al, 2006) has reduced myo-inositol and ascorbic acid levels, suggesting such a connection between these pathways (Torabinejad et al, 2009).…”
Section: Mips1 Impacts Inositol Synthesismentioning
confidence: 99%
See 3 more Smart Citations
“…Evidence exists that a minor pathway to ascorbic acid synthesis could proceed via myo-inositol synthesis (Baig et al, 1970;Radzio et al, 2003;Lorence et al, 2004;Torabinejad et al, 2009). We have previously shown that the vtc4 mutant (Conklin et al, 2006) has reduced myo-inositol and ascorbic acid levels, suggesting such a connection between these pathways (Torabinejad et al, 2009).…”
Section: Mips1 Impacts Inositol Synthesismentioning
confidence: 99%
“…We have previously shown that a loss of function in another gene required for myo-inositol synthesis, Vitamin C-4 (VTC4), results in sensitivity to abscisic acid (ABA), salt, and cold (Torabinejad et al, 2009). To test whether known stress physiological pathways that use myo-inositol signaling (Xiong et al, 2001;Taji et al, 2006) were altered in mips mutants, we produced age-matched seed populations that had been harvested from plants grown at the same time.…”
Section: Mips1 Is Required For Physiological Responsesmentioning
confidence: 99%
See 2 more Smart Citations
“…The main synthetic pathway for AsA in vascular plants is Man (sugars in this study are D series unless designated otherwise)/L-galactose pathway (Smirnoff-Wheeler pathway) (Wheeler et al, 1998), in which the conversion of GDP-Man from Man 1-phosphate (Man 1-P) catalyzed by GDP-Man pyrophosphorylase (GMPP) is a rate-limiting step affecting AsA quantity, as well as several downstream steps (Supplemental Figure 1) (Dowdle et al, 2007;Linster et al, 2007;Torabinejad et al, 2009). VITAMIN C DEFECTIVE1 (VTC1)/CYTOKINESIS DEFECTIVE1 (CYT1; hereafter, VTC1 indicates VTC1/CYT1 protein) has been identified as the major form of GMPP in Arabidopsis, and evidence for its key role in AsA synthesis comes from a number of different studies: In Arabidopsis thaliana, the vtc1-1 mutant, a leaky mutant for the VTC1 gene, exhibits a 70% decrease in AsA level (Conklin et al, 1997(Conklin et al, , 1999) and a CONSTITUTIVE PHO-TOMORPHOGENESIS9 (COP9) signalosome subunit, CSN5B, downregulates AsA level through the degradation of VTC1 in the dark (Wang et al, 2013b).…”
Section: Introductionmentioning
confidence: 99%